Saurauia beluranensis - Hoo, P.K.; Tsen, S.; Damit, A.; Khoo, E.; Colin Ruzelion Maycock; Sugau, J.; Tanggaraju, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Saurauia beluranensis is known only from two occurrences from the Beluran district, in Sungai Tahid and Sungai Sapi Forest Reserve. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 4 km2. Due to land use change, the area and quality of its habitat have declined. The decline is inferred to be continuing as Sungai Tahid is being converted for palm oil plantations and is not within a protected area. Hence, it is assessed as Critically Endangered. Saurauia beluranensis is endemic to Sabah, Malaysia. It is known only from the Beluran district.